TRANSSEXUAL WOMEN IN CONTEMPORARY DISCOURSE: A CASE STUDY - Roberta Siqueira Mocaiber Dieguez (Universidade do Estado do Rio de Janeiro, 2016)
Transsexualism has been increasingly discussed in the media and other means. However, one cannot treat such a broad topic without questioning one of the pillars of society: the difference between sexes. This discussion is necessary, since transsexual individuals contradict the roles of predetermined genders according to biological sex. In this paper, we have made an analysis of a case study of a transsexual woman. A transsexual woman is a person who has been designated as male at birth, but considers herself to be a woman. Throughout the interview, which consisted of 18 questions about the experience of transsexualism, various aspects of the interviewee's discourse were revealed. They pointed to the difficulty on finding her place in society, because individuals only become intelligible in society when they identify themselves with either the male or female gender. In addition, it is assumed that there are only two possible genders, and that they should follow predefined standards. These standards are assumed to have been built from historically established relations of domination. Based on these concepts, transsexual people become marginalized and pathologized by scientific discourse, which creates many difficulties for them to be recognized. Based on the case study, we could also discuss the representations of femininity. After the interview, a content analysis was performed and the results pointed to a quest by the interviewee to find her place in the middle of a gendered and heteronormative society. DOI: 10.12957/demetra.2016.22426